Beneficial bacteria for improving white clover establishment - Sarathchandra, S.U.; Bell, N.L.; Burch, G.; Aalders, L.T.; Eden, T.M. (New Zealand Plant Protection, 2010)
White clover (Trifolium repens) seedlings encounter the adverse impacts of root parasitic nematodes during plant establishment Of these root knot (Meloidogyne trifoliophila) and cyst (Heterodera trifolii) nematodes are well established in the North Island while only the latter is encountered in South Island pastures Once root damage is caused by the nematode the resulting wound can facilitate the entry of root pathogenic fungi into the plant compounding the problem Use of naturally occurring micro organisms to counteract the adverse impacts of nematodes in white clover is an attractive option Bacteria isolated from New Zealand pastures were screened for their beneficial effects on white clover seedling vigour in pot experiments and a field experiment When applied as a drench at sowing several bacterial strains (mostly Bacillus and Pseudomonas) produced significant (P